Learning Management Systems - Thilagam, K.; Barathi, C. (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
Learning Management Systems (LMS) have transformed the education landscape by providing a digital platform for teaching, learning, and assessment. This review paper aims to explore the evolution of LMS, its benefits, features, and applications in education. A comprehensive literature review was conducted to identify the impact of LMS on student learning outcomes, teacher professional development, and institutional effectiveness. The findings suggest that LMS has improved student engagement, motivation, and academic performance. Additionally, LMS has facilitated teacher collaboration, resource sharing, and professional development. However, challenges such as technical issues, cost, and teacher training need to be addressed. Future directions for LMS research and development include artificial intelligence, mobile learning, and gamification. The study concludes that LMS has the potential to enhance education by providing a personalized, flexible, and accessible learning experience.